Dendritic lipopeptide liposomes decorated with dual-targeted proteins. (1st November 2022) - Zhou, Sensen; Li, Cheng; Yuan, Yang; Jiang, Lei; Chen, Weizhi; Jiang, Xiqun
Abstract : A tumor-targeted dendritic lipopeptide liposome was developed to improve the anticancer effect of loaded drugs by enhancing tumor targeting, cancer cell endocytosis and tumor penetration. Abstract : Due to their homing effects, cell and cell membrane-derived nanocarriers have been widely used to enhance drug target delivery. Inspired by the protein-anchored cell membrane architecture, we here report a tumor-targeted liposome, dtDLP, which was constructed through the electrostatic interaction between dendritic lipopeptide liposomes and a dual-targeted recombinant protein, achieving superior tumor homing, cellular endocytotic and penetration abilities. The dual-targeted recombinant protein consists of an anti-epidermal growth factor receptor single domain antibody and a peptide ligand for the integrin αv β3 . dtDLPs substantially reduced macrophage phagocytosis and increased drug internalization in both 4T1 cells and HeLa cells by providing more endocytic pathways. In addition, the dtDLPs showed great penetration ability in both multicellular spheroids and tumor tissues. Due to the improved cancer cellular uptake and tumor penetration, the dtDLPs exhibited a superior anticancer effect in both HeLa and 4T1 tumor-bearing mice. This work will be helpful for the design of cell-specific liposomes with admirable tumor targeting, endocytotic and penetration abilities.